Tycho: Facilitation Support for Groupware User Tests - Grigera, Julián (2021)
Running user tests for groupware requires tracking the progress of multiple users performing co-dependent tasks, while facilitating and observing their coordinated actions. This requirement negatively impacts the main objective of user testing, which is detecting usability flaws. User testing of groupware becomes more challenging when run remotely. Even if there are tools for remote user testing that can get the job done for a single user, they are not prepared for collaborative scenarios. In this paper we argue that tool support for the facilitation of user tests of groupware is missing. Consequently, we propose a method for user tests with tool assistance that makes it possible to automate task synchronization, especially for different workflows that must be run concurrently. We evaluated our proposal by comparing it to a manually facilitated approach during on-site coordinated user tests. The results indicate that, while the task of designing and running user tests with tool support takes more time, it allows the testers to better focus on detecting usability problems.